PERMASALAHAN DAN KONSEKUENSI DESENTRALISASI FISKAL - Siti Fatimah Nurhayati (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2001)
In local autonomy implementation, there are various decentralization processes. One of them is decentralization in fiscal sector. Fiscal decentralization relates to local authority using their own fiscal resource which is supported by financial balance between central and local government. Some problems which is estimated will emerge in fiscal decentralization process is a natural thing for local government which have authority to manage their own household affairs. In addition to emerged problems, there are some decisive factor which is calculated as the something determining the success of decentralization process. Decentralization can also give varying implications toward inter-region development activity.